Larval Nutrition of Silver Barb Barbodes Gonionotus with an Emphasis on Protein-Energy Requirements and Feeding Strategy - Tayag, Carina Miranda (2004)
A series of experiments were conducted to determine the possibility of rearing silver barb larvae on an artificial diet. Prior to the evaluation of artificial diet in rearing silver barb larvae, a study was conducted to determine the changes in the amino acid profile of silver barb from freshly stripped eggs to newly hatched larvae. The result showed that the amino acid pattern changed according to the developmental stages of the fish larvae. The optimum protein requirement of silver barb larvae was determined using five isocaloric diets with varying protein levels (40, 45, 50, 55 and 60% protein). The results showed that the larval growth was highest when they were fed a diet containing 55% protein followed by those fed with 50, 45, 60 and 40% protein. Although the highest survival was obtained among larvae fed on a 50% protein diet, it was not significantly different (P>0.05) from the survival of those fed on a 55% protein diet. In the following study, the optimal protein-energy requirement of silver barb larvae was determined. Six experimental diets containing two levels of protein (50% and 55% protein) and three energy levels (18.8, 19.7 and 20.5 kJ g-') were evaluated. In this study, larvae fed a diet containing 50% protein with 19.7 kJ g" energy obtained the best growth and highest survival. This level was found to be optimum for growth and maintenance of the larvae. An experiment was also conducted to find the best feeding rate for silver barb larvae. The present study showed a significant relationship between feeding rate and growth of the larvae. Based on growth, feed efficiency and survival, an optimal feeding rate of 45% BW d-' was found for silver barb larvae. Lastly, this study revealed that silver barb larvae are visual feeder. Feeding the larvae throughout the day (day and night) did not give any beneficial effect for the larvae and resulted in lower growth and survival. This study suggested that feeding the larvae four times during daytime was the best feeding frequency for silver barb larviculture.